Labour‐Based Justifications of Intellectual Property and the Problem of Disruptive Innovations. - Duncan, Samuel (Journal of Applied Philosophy, 2020)
Justifying intellectual property on the basis of labour is an understandably popular strategy, but there is a tension in basing some intellectual property claims on labour that has gone largely unnoticed in treatments of the subject: many forms of innovation cause people to lose their jobs, which seriously hampers the ability of those who lose work to productively use their own labour. This article shows that even under Lockean and other labour‐based justifications of intellectual property rights those who claim property rights to innovations of this type have special obligations to compensate those who lose work because of their inventions. By examining the problem that such innovations create, I hope to contribute to larger debates about automation and the job losses it often brings. Lockean and other labour‐based theories of intellectual property are generally taken to secure strong, noninstrumental rights to intellectual property if they are successful. So, if even these theories imply that those who profit from the innovations driving automation have special obligations to those left jobless by it, that is strong evidence that they do in fact have such obligations.